Anonymous vs. non-anonymous administration of depression scales in elite athletes: a meta-analysis - Harenberg, S.; Ouellet-Pizer, C.; Nieto, M.; Kuo, L.; Vosloo, J.; Keenan, L.; Wilson, S. (International Review of Sport and Exercise Psychology, 2022)
Depressive symptoms are highly prevalent in elite athletes, even though physical activity can be a protective factor. Estimations from studies exploring the prevalence of depressive symptoms range substantially, from 1.1% to 32.2%. To date, one can only speculate why this variability exists. Theoretically, non-anonymous screenings may lead to more underreporting compared to anonymous assessments, due to various environmental and personal factors (e.g. social desirability bias, mental health stigma). Yet, there is an absence of exploration whether anonymous or non-anonymous screenings for depressive symptoms yield different prevalence estimations. This is the purpose of the present study. We performed a meta-analysis on 31 cross-sectional studies (searched in SPORTDiscus, PubMed, PsycINFO, CINAHL) with a total sample size of 9776 elite athletes. Prevalence ranged from 0%to 30.7%, with a pooled prevalence of 15.3%. Large heterogeneity and average quality of articles were detected. Anonymity was a significant moderator, showing that studies with anonymous assessments (22.3%) estimated almost double the prevalence compared to non-anonymous screenings (11.4%). As such, identifiable mental health screenings may detect about half of the athletes suffering from clinically relevant depressive symptoms. We discuss several underlying factors and provide recommendations to improve the effectiveness of mental health screenings in elite athletes.